Polimorfismos no genoma mitocondrial associados à Esclerose Lateral Amiotrófica - Santos, Ilda Manuelly Da Silva [UNIFESP] (2019)
Mitochondria play central roles in cell maintenance that goes beyond energy production, such as regulation of intracellular Calcium and apoptosis. Although mitochondrial alterations have been associated with Amyotrophic Lateral Sclerosis (ALS) and mutations in the mitochondrial genome have been identified, the association of these with Amyotrophic Lateral Sclerosis (ALS) does not seem clear. ALS associated mutations in the mitochondrial genome and verify the distribution of mitochondrial haplogroups in ALS we performed a pilot study on 134 samples of familial and sporadic ALS from the Pennsylvania State University Hershey Health System (Institute for Personalized Medicine) in collaboration with the group of Prof. James R. Broach. The comparative analysis of patient and reference sequences reveals one SNV and insertion associated with ALS with p <0.05 and odds ratios >1). This mutation is located in the control region of the mitochondrial DNA. We observed that control region mutations here identified are also associated with cancer e our data shows that European ancestry represents 91.70% of samples of which 43.28% corresponding to haplogroup H. These preliminary results suggest the existence of mitochondrial genome mutations associated with ALS and that bias towards specific haplogroups observed are consistent with findings on other neurodegenerative diseases. Future research is needed to strengthen SNV associations here observed and might shed light on ethnicity bias as observed in ALS.